Simultaneous Presentation of Definite Vestibular Migraine and Definite Ménière's Disease: Overlapping Syndrome of Two Diseases - Murofushi, Toshihisa; Tsubota, Masahito; Kitao, Kyoko; Yoshimura, Eriko (Frontiers in Neurology, 2018)
Objectives: To review the clinical records of patients that exhibited the clinical features of both vestibular migraine (VM) and Ménière’s disease (MD) during each episodic vertigo attack and to discuss the possible pathophysiology of such combination of symptoms. Subjects: Ten patients that were selected according to criteria based on a combination of the diagnostic criteria for definite MD and VM (9 females and one male, age: 22-54 years) were enrolled. They were required to show features of both diseases in each vertigo attack. Methods: The patients’ medical histories and pure-tone audiometry, cervical vestibular evoked myogenic potential (cVEMP), video head-impulse test (vHIT), and caloric test results were examined. cVEMP was recorded using 500 Hz and 1000 Hz short tone bursts (125dBSPL, air-conducted), 500 Hz-1000 Hz cVEMP slope, an index of endolymphatic hydrops in the saccule was calculated using normalized amplitudes of p13-n23. For performing vHIT, each subject was seated 1.5 m in front of a target and asked to keep watching it as their head was passively rotated by the examiner. Their eye movements were evaluated using video-oculography while their head movements were recorded using inertial sensors. Results: The patients were predominantly female. On average, the onset of migrainous headaches occurred 9 years earlier than the onset of vertigo attacks. All of the patients but one had migraines with auras. Five of the 10 patients had a family history of vertigo attacks accompanied by both migrainous and auditory symptoms. The patients mainly displayed hearing loss at low frequencies. Nine patients exhibited 500 Hz-1000 Hz cVEMP slope < -19.9, which was suggestive of endolymphatic hydrops. None of the patients who underwent vHIT showed abnormal canal function. One patient showed unilaterally decreased caloric responses. Conclusions: These patients presented with simultaneous MD and VM signs/symptoms might be referred to “VM/MD overlapping syndrome (VM/MD-OS)” as a new clinical syndrome.